Implementasi Pemberdayaan Aparatur Sipil Negara (ASN) Pada Dinas Pertanian Dan Perkebunan Di Kabupaten Sintang - Chandra, Yogi; Martoyo, Martoyo; Yohanes, Yulius (Jurnal Multidisiplin Dehasen (MUDE), 2025)
Writing a thesis in this study entitled: "Empowerment of State Civil Servants (ASN) in the Department of Agriculture, Fisheries and Food Security in Sintang Regency". The purpose of this study is to describe the implementation of apparatus empowerment in the Department of Agriculture, Fisheries and Food Security in Sintang Regency. This is to find out the factors that influence the empowerment of the State Civil Apparatus within the Department of Agriculture, Fisheries and Food Security in Sintang Regency. Research results In empowering the employee apparatus at the Department of Agriculture, Fisheries and Food Security, Sintang Regency, giving trust by the leadership in granting authority to subordinates is always used as the basis for carrying out tasks in the service environment so that employees with their obligations convey accountability in accordance with the program orientation specified in job description. Besides the authority given by the leadership is clear according to the mechanism that has been determined, besides that the provision of support by the leadership of the staff feels motivated because of the attention given by the superior so that the expected performance can be achieved. Capability of Civil Servants in the Department of Agriculture, Fisheries and District Food Security The hedgehog is low. This is due to the large number of staff shortages. Therefore, prioritizing placement in areas that are quite urgent. An adequate number of employees does not guarantee the smooth running of services aimed at the community if these employees do not understand the substance of their duties properly. Therefore, the delegation of authority must be based on needs by referring to the needs of each division in the service. The delegation of authority based on needs can foster empowerment so as to spur the morale of the employees concerned.